APLIKASI SISTEM PELAYANAN MASYARAKAT BERBASIS ANDROID - Rasapta, Diki (Journal of Research and Publication Innovation, 2024)
Public service is an activity (serving) or providing services to people who have an interest in an agency referring to the main rules and procedures that have been determined. Currently, public service procedures in the reporting section in RW 02 are still running manually and have many shortcomings and weaknesses, which has caused the performance of the RW 02 organization to be hampered and unable to support the needs desired by the existing community, starting from the process of inputting reports. to report management which takes quite a lot of time. This research aims to analyze and design a web-based reporting information system that is needed by the RW 02 community. Design a reporting information system using quantitative methods to get a picture of the identity and characteristics of targets as well as responses and expectations regarding planned application design activities. The result of this research is a mobile (smart phone) based application that can be used easily by administrators and residents in carrying out administrative governance. The function designed in this system consists of reporting violations in the RW 02 area as well as tracking inputted reports and management. existing reports. From the research conducted, it can be concluded that the Android application for the public complaint service system can be a solution and improve the quality of services in the area. This complaint system certainly has shortcomings.